2006
DOI: 10.1007/s11908-006-0063-z
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonitis in human cytomegalovirus infection

Abstract: Human cytomegalovirus (HCMV) is a beta herpes virus with a double stranded DNA genome of 240kbp. The virus is prevalent and establishes a latent infection in most adults. HCMV is an opportunistic pathogen for patients with impaired cellular immunity. HCMV pneumonia is a common presentation of HCMV disease in immunocompromised patients. The incidence of HCMV pneumonitis can be as high as 90% in lung transplant recipients. This paper takes a fresh look at the challenging perspectives of molecular, immunologic, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Cytomegalovirus (CMV) is a major pathogenic microbe in immunocompromised individuals, and CMV pneumonia (CMVp) is a critical complication because of the high fatality. 1,2 The clinical findings of CMVp have been well documented; 3,4 however, how CMV infection causes pulmonary lesions is not yet well understood.…”
Section: Pulmonary Cytomegalovirus (Cmv) Infection Causes Fatal CMV Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytomegalovirus (CMV) is a major pathogenic microbe in immunocompromised individuals, and CMV pneumonia (CMVp) is a critical complication because of the high fatality. 1,2 The clinical findings of CMVp have been well documented; 3,4 however, how CMV infection causes pulmonary lesions is not yet well understood.…”
Section: Pulmonary Cytomegalovirus (Cmv) Infection Causes Fatal CMV Pmentioning
confidence: 99%
“…On the basis of viral tropism and the expression of TGF-b1, ITGB6, and IL-8, we conclude that CMV-infected pulmonary cells play an important role in the development of diverse CMVp patterns.Key words: chromogenic in situ hybridization, cytomegalovirus pneumonia, double immunostain, integrin b6, interleukin-8, transforming growth factor-b1Cytomegalovirus (CMV) is a major pathogenic microbe in immunocompromised individuals, and CMV pneumonia (CMVp) is a critical complication because of the high fatality. 1,2 The clinical findings of CMVp have been well documented; 3,4 however, how CMV infection causes pulmonary lesions is not yet well understood.Cytomegalovirus pneumonia, a secondary interstitial pneumonia (IP), exhibits various histopathological characteristics, i.e., focal or diffuse interstitial lesions with/without hemorrhage, hyaline membrane, and necrobiosis. 5-7 It has been reported that CMV infects a wide variety of cell types, including pneumocytes, fibroblasts, macrophages, and endothelial cells in the lung.…”
mentioning
confidence: 99%
“…CMV infection occurs most commonly in the setting of lung transplantation, bone marrow, and other organ transplantation, with rates typically between 53% and 75% but reported as high as 90%. 89,111,112 Clinical presentation includes fever, cough, and hypoxemia. Infection in the setting of immune compromise is likely caused by reactivation of latent infection.…”
Section: And Other Viral Pneumoniasmentioning
confidence: 99%